Development of Indole Alkaloid-Type Dual Immune Checkpoint Inhibitors Against CTLA-4 and PD-L1 Based on Diversity-Enhanced Extracts - Suzuki, Yoshihide; Ichinohe, Keisuke; Sugawara, Akihiro; Kida, Shinya; Murase, Shinya; Zhang, Jing; Yamada, Osamu; Hattori, Toshio; Oshima, Yoshiteru; Kikuchi, Haruhisa (Frontiers in Chemistry, 2021)
Cancer immunotherapy involves the use of the immune system for cancer treatment. Recently, immune checkpoint-blocking antibodies have become integral for the treatment of some cancers. However, small molecules exhibit advantages over monoclonal antibody drugs, such as cell penetration, long half-life, and low manufacturing costs, and the possibility of oral administration. Thus, it is imperative to develop small-molecule immune checkpoint inhibitors. Previously, we have screened a library of synthetic indole-alkaloid-type compounds, which are produced by diversity-enhanced extracts of Japanese cornelian cherry, and reported that an unnatural pentacyclic compound inhibits CTLA-4 gene expression. In this study, immune checkpoint inhibitors with increased potency were developed by introducing substituents and conversion of functional groups based on the unnatural pentacyclic compound. The developed compounds suppressed not only CTLA-4 and PD-L1 gene expression but also protein expression on the cell surface. Their efficacy was not as potent as that of the existing small-molecule immune checkpoint inhibitors, but, to the best of our knowledge, the developed compounds are the first reported dual small-molecule inhibitors of CTLA-4 and PD-L1.